Atypical cytomegalovirus retinitis in non-Hodgkin's lymphoma. (3rd August 2015) - Tyagi, Mudit; Ambiya, Vikas; Mathai, Annie; Narayanan, Raja
Abstract : A 54-year-old woman, a known case of non-Hodgkin's lymphoma (NHL) in complete remission, presented with floaters and diminution of vision in her left eye. The eye had vitritis with non-haemorrhagic retinitis mimicking intraocular lymphoma and acute retinal necrosis. A vitreous sample was positive for cytomegalovirus (CMV) and herpes simplex virus 1 (HSV-1) DNA by PCR. The possibility of intraocular lymphoma was not confirmed by the immunohistochemistry of the vitreous sample. The patient had a relapse of NHL along with rapid deterioration of vision in her left eye to no perception of light, due to optic nerve involvement. The right eye developed a new patch of focal haemorrhagic retinitis threatening the fovea. Based on the laboratory results and the clinical findings, she was successfully managed as a case of bilateral CMV retinitis and the vision in her right eye was salvaged.